ANALISIS PELAYANAN PUBLIK PADA BADAN PERPUSTAKAAN, ARSIP DAN DOKUMENTASI DAERAH PROVINSI SULAWESI TENGAH - Agian, Berlianus (Katalogis, 2013)
This research aimed at analyzing the public service and the influencing factors within the Provincial Library, Archives, and Documentation Office of Central Sulawesi. The theoretical review in this research is Tangible, Reliability, Responsiveness, Assurance, Empathy. This research used descriptive qualitative method. The research site was within the Provincial Library, Archives, and Documentation Office of Central Sulawesi. The informants were selected by using two techniques, namely: Purposive, that is, choosing the sample by having specific reasons, and Accidental, that is, taking whoever the research met. The purposive technique gave priority to those who served, the librarians within the Provincial Library, Archives, and Documentation Office of Central Sulawesi, and the accidentally-selected informants were the service users. The data collection techniques were observation, interview, and documentation. The researcher used interpretation analysis technique which finds out the meaning of the problem, case, condition, and situation. The research showed that the public service within the Provincial Library, Archives, and Documentation Office of Central Sulawesi, based on the indicators: a) TangibleÂ  b) Reliability, c) Responsiveness, d) Assurance, e) Empathy did not work well as expected. The determinant factors in the public service within the Provincial Library, Archives, and Documentation Office of Central Sulawesi were a) Human Resources, b) Discipline, and c) Leader.